Gender gaps at the top: Does board composition affect executive compensation?. (August 2019) - Cook, Alison; Ingersoll, Alicia R; Glass, Christy
Will adding women to the board of directors reduce firm gender pay disparities? Our research suggests 'no' … and 'yes.' It is not a matter of simply adding more women to the board or integrating women into key board committees that moves the needle. If firms really want to stimulate change through board diversity, then they need to empower female directors and place them in key leadership roles. We find that women's integration on the board of directors and on the compensation committee has no significant impact on lessening the compensation gap within the top executive team. However, when women influence compensation decisions through service as the chair of the compensation committee, the top executive compensation gap is diminished. Our analysis relies on a dataset built by the authors of all top management team executives and board members from the S&P 500 from 2009–2013. We test three mechanisms that may enable women to overcome limitations with respect to pay equity: (i) integration, (ii) direct decision making and (iii) influence. Our findings suggest that not all types of power are equal; the more direct influence women have over compensation decisions, the smaller the compensation gap.